Minorities, Minority Rights and Internal Self-Determination - Barten, Ulrike; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The book questions the classic idea of self-determination – the right to self-determination is a right of peoples, not of minorities – by examining the content of the right to self-determination and the content of minority rights. Self-determination has four dimensions: the political, the economic, the social and the cultural dimensions. Minorities have minority rights that touch on most aspects of life as a member of a minority. If there is an overlap between minority rights and the different dimensions of self-determination, the concept that the right to self-determination is only applicable to peoples loses credibility. No global and general conclusion is envisaged; there are restrictions in place. The work is limited to the European framework and is further restricted to classic minorities. The argument is based on a legitimacy and justice approach. The analysis in this book shows that some minority rights overlap with the different dimensions of internal self-determination. In short, classic minorities in Europe have a right to internal self-determination.
Part I: Introduction -- The international relations framework -- Classic sources on minority rights and self-determination -- Non-state actors and non-binding instruments -- Legitimacy and justice -- Legitimacy and justice of non-binding instruments -- Part II: Minority rights -- Minority, people, nation -- Understanding self-determination -- Part III: Minority rights and internal self-determination -- Putting together the pieces -- Part IV: Conclusion -- Summary.
Keywords: Human rights; International relations; Human Rights; International Relations